Utilization of Cassava Peel as Substrate for Production of Biofertilizer and Its Effect on the Growth of Millet - Yusuf, Obadiah Saveni; Abershi, Ajiduku Leyoa; Chuanu, Solomon; Ngabea, Nasiru Audu; Bappa, Lipana Dorcas; Mafe, Alice Njolke; Idris, Maina Sumaiya (Darul Yasin Al Sys, 2024)
The quality of the carrier is critical in influencing microbial load and shelf life of biofertilizers. Cassava peels are abundant and have little economic value, making them ideal for use as biofertilizer carrier materials. The carrier material supported the growth of the test organism, thus suggesting the presence of nutrients and absence of toxicity. During isolation and culturing of bacteria, three (3) grams of soil sample was measured and diluted with 100ml of distilled water, and mixed well to get soil suspension. Ten (10) ml of the soil suspension was poured in the first test tube and shake well, 1ml of the first test tube was transferred into the second test tube containing nine (9) ml of sterile distilled water aseptically to get dilution. One (1)ml of the suspension from the second test-tube was transferred to third test tube also containing 9ml of sterile distilled water aseptically, 1ml of the soil suspension was transferred from the third test tube to the fourth test tube,1ml of the soil suspension was transferred from the fourth test tube was transferred to the fifth test tube,1ml of the soil suspension from the fifth soil suspension was also transferred to the sixth test tube, another 1ml from the sixth soil suspension was also transferred to seventh test tube aseptically. Soil sample from test tube 4, 5, and 6 was inoculated in yeast extract media and was incubated for 24 hours. The result shows that at 2DAP, 3DAP, 4DAP, 5DAP, AND 6DAP there is statistical significant difference between the treatment and control but at 7DAP, 8DAP, 9DAP AND 10DAP there is no statistical significant difference between the treatment and control but also at 11DAP there is statistical significant difference between the treatment and the control and at 10DAG, 12DAG, 14DAG, 16DAG, 18DAG, AND 20DAG there is no statistical significant difference between the treatment and control but at 22DAG there is statistical significant difference between the treatment and control at 24DAG there is no statistical significant difference between the treatment and the control. And at 26DAG there is statistical significant difference between the treatment and the control but also at 28DAG there is no statistical significant difference between the treatment and the control using fisher’s least significant difference test. Biofertilizer is a relevant alternative for disposal of this waste and even enables the act of converting wastes to wealth.